(untitled) (Communications in Computational Chemistry, 2025)
Two-dimensional (2D) Ruddlesden-Popper (RP) perovskites have been intensively investigated due to their superior stability and outstanding optoelectronic properties. Although A-site doping in quasi-2D RP-phase perovskites has been extensively studied, the effect of X-site doping remains unknown. Using first-principles calculations, this work demonstrates that SCN^- substitution in Cs_2Pb(SCN)_2Br_2 induces a structural transformation from isotropic to anisotropic through octahedral tilting along the b-axis, reducing octahedral spacing from 5.17 to 4.88 Å. This structural modification enhances carrier mobility, dramatically increases exciton binding energy from 30.47 to 145.39 meV, and improves defect tolerance compared to pristine Cs_2PbBr_4. These modifications synergistically suppress non-radiative recombination pathways while promoting radiative processes, so that improve its performance as a promising light-emitting diode (LED) material. These findings establish pseudo-halogen substitution as a promising strategy for optimizing carrier transport and radiative efficiency in low-dimensional perovskite LED devices.